Instability of 2DEG interacting with drifting 3DEG - Boiko, I.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
Dispersion law is studied for high-frequency longitudinal plasma waves in 2DEG (the plane z = 0), separated by thin dielectric layer from half-limited 3DEG. It is shown that drift of 3DEG provokes for special conditions instability of considered plasma waves.